Spatial variation of date production in Al-Zahdi and Al-Khistawi in Iraq for the duration (2010-2019) and its future predictions - Kazim, Amal Sabah Hassan (Al-Adab Journal, 2021)
The study is part of agricultural studies that address the productivity problem of the two most prominent types of dates in areas known to have been cultivated since ancient times. Palm cultivation and date production are constantly deteriorating in most of its production areas, so the study summarized the spatial variation of the production of Al-Zahdi and Al-Khistawi in iraq's production provinces for the period (2010-2019), to determine the volume of production and future predictions using approved statistical methods.The study was followed by two main approaches (geospatial analysis method) to determine spatial variations in production (and the inference analysis method) as the simple linear regression model was chosen to find the predictive value of its production in the study area by relying on a time series of production quantity (2010-2019) by provinces and for the two categories through a set of results such as correlation value coefficient and F value of the overall morality of the regression equation and the value (t) of the partial parameters of the parameters. According to this model, the production of the two categories was predicted until 2025, and the results showed a spatial and temporal variation in production at the level of the producing provinces. The hierarchical cluster analysis was used to divide the provinces into clusters with common elements and characteristics in production and which is unique from the rest of the provinces by producing one of the categories, indicating the specificity of these provinces in their production in quantity and quality. Based on the data available from the Ministry of Planning/Central Bureau of Statistics/Directorate of Agricultural Statistics on production volumes at the level of the provinces producing for the calculated period.The study included many tables, charts and illustrative maps, the study also came up with a number of conclusions and proposals, and the study relied on many important sources in the topic.